2017
DOI: 10.1111/hel.12400
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial resistance and the success of tailored triple therapy in Helicobacter pylori strains isolated from Slovenian children

Abstract: BackgroundPrimary Helicobacter pylori (H. pylori) infection occurs predominantly in childhood. Antimicrobial resistance is the leading cause for H. pylori eradication failure. The aims of this study were (i) to establish for the first time the antimicrobial resistance of H. pylori strains in infected Slovenian children not previously treated for H. pylori infection and (ii) to evaluate the effectiveness of tailored triple therapy, assuming that eradication rate with tailored triple therapy will be >90%.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 25 publications
3
24
2
3
Order By: Relevance
“…Similar increasing trends in CH resistance in children was observed by other authors from Europe and Asia [ 22 , 23 , 24 ]. The single resistance of H. pylori strains isolated from children to MET in our region remains stable, but high (from 28.6% in the period from 2008–2012 to current 31%), similar to other European countries (15–30%), but it is much higher in Iran (60%) and in China (68%) [ 13 , 20 , 21 , 22 , 25 , 26 , 27 , 28 ]. The increase in dual resistance to CH and MET from 14% to 35% detected in our study is particularly alarming.…”
Section: Discussionsupporting
confidence: 62%
“…Similar increasing trends in CH resistance in children was observed by other authors from Europe and Asia [ 22 , 23 , 24 ]. The single resistance of H. pylori strains isolated from children to MET in our region remains stable, but high (from 28.6% in the period from 2008–2012 to current 31%), similar to other European countries (15–30%), but it is much higher in Iran (60%) and in China (68%) [ 13 , 20 , 21 , 22 , 25 , 26 , 27 , 28 ]. The increase in dual resistance to CH and MET from 14% to 35% detected in our study is particularly alarming.…”
Section: Discussionsupporting
confidence: 62%
“…As the results in this study, the amoxicillin resistance rate of pediatric isolates was reported to be low (<1%) in 2010 . Although high amoxicillin resistance rates of pediatric H pylori were reported in Korea (24.2% in 2005‐2009) and in Brazil (10.4% in 2008‐2009) even with cutoff values of 0.5 μg/mL and 2 μg/mL, respectively, the resistance rate remains low in countries with a previous low rate, including Taiwan . In this study, the amoxicillin‐resistant rate of pediatric H pylori was 4.9% measured by the E test in a 10‐year surveillance (2009‐2018).…”
Section: Discussionmentioning
confidence: 46%
“…However, a marked reduction in eradication rate has been reported if there is coresistance to clarithromycin and metronidazole . The overall coresistance rate to clarithromycin and metronidazole of pediatric H pylori isolates after 2000 ranged 7.7%‐11.5% worldwide . Surprisingly, a very high coresistance rate of both drugs was found (50.7%) in pediatric isolates in Beijing from 2009 to 2010 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations